Exposure to light at night (LAN) and risk of breast cancer: a systematic review and meta-analysis - Lai, KY; Sarkar, C; Ni, MY; Cheung, LWT; Gallacher, J; Webster, C (Elsevier, 2020)
BACKGROUND: With the unprecedented urbanization light pollution is a ubiquitous problem, with accumulating evidence on the links between exposure to light at night (LAN) and breast cancer risk. We conducted a systematic review and meta-analysis of published studies on the associations between LAN exposure and breast cancer risk.